PREVALENCE OF INCIDENTAL THYROID NODULES IN ULTRASOUND STUDIES OF DOGS WITH HYPERCALCEMIA (2008–2013). Issue 1 (17th June 2014) - Pollard, Rachel E.; Bohannon, Laurie K.; Feldman, Edward C.
<x xml:space="preserve">Abstract</x> Ultrasound is commonly used to evaluate the cervical region in dogs with hypercalcemia due to suspected hyperparathyroidism. Incidental thyroid nodules may be detected during these studies, however little information has been published to guide clinical decision‐making when this occurs. The purpose of this cross‐sectional study was to determine the prevalence of incidental thyroid nodules in hypercalcemic dogs undergoing cervical ultrasound at our hospital during the period of 2008–2013. Dogs with a palpable neck mass were excluded. Cervical ultrasound images for each dog were retrieved and reviewed by a board certified veterinary radiologist who was unaware of patient outcome. Presence, number, and dimensions of thyroid nodules were recorded. Results of thyroid nodule aspirate, biopsy or necropsy were recorded from medical records when available. Ninety‐one dogs met inclusion criteria. Of these, 14/91 (15%) dogs had at least one thyroid nodule. Mean (± standard deviation) thyroid gland nodule length, width, and height were 1.51 ± 0.74, 0.96 ± 0.73, and 0.75 ± 0.36 cm, respectively. A histologic diagnosis was available for the incidental thyroid lesions in eight dogs, including one dog with two nodules. Confirmed diagnoses for these nodules were thyroid cyst (3/9, 33%), thyroid adenoma (3/9, 33%), thyroid adenocarcinoma (2/9, 22%) and nodular hyperplasia (1/9, 11%). Findings indicated that incidental thyroid nodules may be present in hypercalcemic dogs with no palpable neck mass and no clinical signs of thyroid disease. Some of these nodules may be malignant and therefore a recommendation for cytology or biopsy may be justified.